Identification of Learning Resources on Environment Learning In Department of Biology, Faculty of Mathematics Natural Sciences, Universitas Negeri Makassar - Arsal, Andi Faridah; Dirawan, Gufran D.; Hala, Yusminah; Tahmir, Suradi; Arifin, Arifah Novia; Bahri, Arsad (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2017)
This study aims: (1) to identify the main support system in the design of environment-based learning in the Jurusan Biologi Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar. (2) To know the utilization of environment-based learning resources in the Jurusan Biologi Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar. Through the Needs Assessment instrument in the form of field observation, questionnaire survey, and interviews on lecturers and students identified the problem to determine the appropriate action for the next stage, so that the learning design will be the best solution. The results obtained that (1) Jurusan Biologi UNM has two locations or major areas that are very supportive of environment-based learning with their respective characteristics. The two areas are Biology Experiment Garden and Library Discussion Platform Biology Department FMIPA UNM. (2) Some subjects have utilized environment-based learning resources in the Jurusan Biologi FMIPA UNM. Solutions from the results of the identification obtained are among others; (1) Jurusan Biologi can be used as a place of learning, learning resources, and as a medium of learning in the design of environment-based learning. (2) Jurusan Biologi can be used as a comfortable and enjoyable learning environment for all academic community (3) Environmental Based Learning Design in Jurusan Biologi can be done in almost all courses by increasing the role of lecturer as a facilitator.